CORPORATE INTERNAL GOVERNANCE AND CORPORATE PERFORMANCE: CORPORATE SOCIAL RESPONSIBILITY AS A MODERATION - Betaria Betaria (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Purpose - The purpose of this research is to analyze the moderating role of corporate social responsibility in the relationship of internal corporate governance (ICG) and firm performance. Research Method – The sample consists of 48 companies listed on the Indonesia Stock Exchange from 2017-2021 which are taken by purposive sampling method. Data analysis method used in this study is panel data regress. Findings - The results show that CEO Power, board independence, managerial ownership, ownership concentration and CSR have no effect on the dependent variable, while board size and audit quality are negatively related to firm performance. The results of the study show that CSR can strengthen the relationship between the board independence, board size and managerial ownership on firm performance, CEO power, ownership concentration and audit quality are not affected by CSR on firm performance. Implication - CSR practices usually involve corporate governance to participate in social and environmental activities. ICG is an important body to control and monitor the corporate social practices.